ANALISIS PERSEPSI MAHASISWA PEROKOK AKTIF DAN VAPE DALAM MENANGGAPI PERINGATAN BAHAYA MEROKOK PADA KEMASAN (Studi Mahasiswa FISIP UPNVJ Periode 2021-2022) - Fikri Ajie Syaputra (2023)
Many ignore the risks of the dangers of smoking, especially students, they still find many of these reasons because they are more relaxed and calm when smoking, and also with some students who know the dangers of smoking they switch to vape or pods. This phenomenon prompted researchers to examine the Perception Analysis of Active Smokers and Vape in Responding to Warnings about the Dangers of Smoking on Packages using Semantic Theory. This study aims to be a way to increase awareness of active smoking students about the dangers of smoking through warnings on packages and to find out how big the impact of warnings on the dangers of smoking on packages is for active smokers. The theory used in this study uses semantic theory with qualitative research methods. There were 10 UPNVJ students who were interviewed. The results of the study concluded that perceptions by all informants about warnings about the dangers of smoking just ignored them, but other than that the informants regarding warnings about the dangers of smoking on packages could increase awareness of health but still had no impact on active smokers because smoking had become their need.